Association of Palm gene mutations with structure and function of paralemmin proteins in Lori-Bakhtiari and Zel sheep Breeds - Zare, Masoomeh; Sadeghi, Mostafa; Ahmadpanah, Javad; Safari, Abbas; Moridi, Misagh (Acta Scientiarum. Animal Sciences, 2022)
The aim of current study was to survey genetic variability of PALM gene’s exon 3 and 4 by PCR-SSCP and DNA sequencing in Zel and Lori Bakhtiari sheep breeds. The SIFT (Sorting Intolerant from Tolerant) and PHyre2 program were used to predict the possible impact of amino acid substitutions on performance and structure of the paralemmin protein. A total of 140 animal’s from 2 Iranian sheep breeds with different fat metabolisms, Lori-Bakhtiari and Zel sheep breeds were considered. The results showed that there are two polymorphic sites including a nonsynonymous substitution and an insertion mutation (49bp). Non-synonymous mutation deduced Thr20Ala amino acid exchange and ensuing two different structures for paralemmin protein that could be potentially affect protein structure and function during the interaction with glutamate in the cytosolic surface of plasma membrane. PALM gene, according to evolutionary path, is classified into two separate categories. In first covey, Gallus gallus and in second one, other species in several branches, so that the sequence of cow and sheep is placed in a sub-branch which forms a clade beside goat. Comparison of illustrated coding region sequences, PALM gene among different species, is of orthologous which are derived from a common ancestor.